Hallelujah (1929) de King Vidor : naissance de la voix afro-américaine à Hollywood - Jean-Marie Lecomte (Revue LISA)
Hallelujah and Hearts in Dixie were the first all-black cast, talking and singing pictures to be produced in Hollywood. Although conceived as a Movietone synchronized sound film, King Vidor’s Hallelujah had to be shot silent and dubbed afterwards. The added sound-track revolutionized the way pictures were perceived. Avoiding both popular imagery and musical fantasy, Vidor achieved what might be called “lyrical social realism”, a blend of subjective vision and objective reality. He extracted the verbal artefacts of negritude found in the Black communities of his Texan childhood while keeping them within a documentary format. To appreciate the full impact the movie made in 1929, one must set it in the proper context of American film in the nineteen-twenties when “colored” characters had a limited segregated place, like silent images in a picture-book. The film’s verbal flux runs like a metaphoric undercurrent displacing visual stereotypy. Hallelujah’s characters (mostly played by untrained actors) transcend the limitations of their visual representation through the poetics of voice. Black Americans are not patronized, but shot with Vidor’s particular brand of subjective realism suffused with folk poetry, they become human.